“Here You Have to Play Dead in Order to Live”. The Production of the Presence in the Local Social Area of a Small City of Corrientes Province - Ré, Valeria (Universidad del Rosario, 2021)
The article explores the meanings of the practices of in-visibilization in local dynamics of the small city of Curuzú Cuatiá, located in the region of the Argentine coast, in the southerm center of the province of Corrientes. It analyzes the elaboration of the presence and its effects on the production of differences and the reproduction of social inequalities. This work describes some rituals commemorating the anniversary of its foundation and particularly the extraordinary celebrations for its Bicentennial. The central axis is to establish relationships between the elaboration of the presence and the instances of legitimization of dominant visions at a local level.